Pendekatan Hibrida dalam Menghadapi Dilema Globalisasi dan Autarki di Sektor Pertahanan Indonesia - Ledy Seftiana; Ivan Yulivan; Djoko Andreas Navalino (Lembaga Kajian Pertahanan Strategis, 2025)
This research explores the tension between globalisation and autarky in Indonesia's defence sector and its implications for national security. Using a qualitative case study approach, this research analyses three main events: US arms embargo, Minimum Essential Force (MEF) policy, and KFX/IFX project. The study integrates the theories of Economic Security, Defence Diplomacy, Realism, Complex Interdependence and National Security to evaluate the impact of global dependence and strategic independence. The results show that a hybrid approach, which integrates the advantages of globalisation and autarchy, is the optimal solution for Indonesia to strengthen national security and maintain strategic autonomy amid global geopolitical challenges.